A Stage-wise Stationary Monocular Visual Control Method for Assembly Robot - Hu, Xiaoping; Xiao, Dongming (Recent Advances in Electrical & Electronic Engineering, 2018)
Background: The stationary monocular visual control is a major mode of robot assembly. In this mode, the viewing field is stationary and the target is not detached. Methods: Self-calibration based on the fundamental matrix is first performed on the camera to obtain its linear interior parameters in this paper. Next, a novel stage-wise visual control method is proposed, which adopts different control strategies at different stages. Results: The location-based visual control strategy is used for the vertical plane, and the image-based visual control strategy is used for the horizontal plane. Guidance experiment is then conducted to verify the accuracy and effectiveness of the proposed control method.
Keywords: stationary monocular vision